DINAMIKA SOSIAL SEBUAH DESA DI PINGGIRAN KOTA (STUDI KASUS MAGUWOHARJO, DIY) - Gutomo Bayu Aji (LIPI Press, 2009)
Based on a research conducted in Maguwoharjo village, this article discusses the impact of regional reclassification from rural to rural-urban area. Without a good plan, urban expansion could create a problem of unplanned regional development, as well as environmental degradation. On the non-physical side, changes in rural to rural-urban has led to the emergence in main industry shifts from agricultural to services sectors. It also creates potential conflict as a result of in-migration to the region. Such problems would not be in existence if the development of urban region was wellplanned designed with the use of collaborative management that includes the government, private sectors and the society. Keywords: Urban expansion, urban fringe, social change